Fiebre de leche - Sánchez González, Jorge Manuel 1951-2015 (1994)
Milk fever. A review. Milk fever is an imbalance in calcium metabolism affecting specially high producing dairy cows. lt is caused by are duction in the capacity of hormonal receptors to activate the calcium homeostatic mechanisms. Hence, when plasma calcium level drops below 5 mg/100 mL the animal dies. Factors affecting the animal susceptibility to this metabolic desorder are feed, animal age, breed, level of production and individual factors. Although, the average incidence is 3 to 4% and mortality is low; milk fever is related to several diseases. Treatment with borogluconate gives excelent results specially if cows are treated durign the first stages of the metabolic desorder. Feeding low calcium diets for two weeks prior to freshening followed by diets with high contents of this mineral during lactation help to prevent milk fever. Alternativety, high dosis of vitamin D in the diet or vitamin D analogs injected before parfurition help to prevent it. Acidogenic salts like ammonium cloride, ammonium sulfate, magnesium chloride and calcium chloride are being also used with success to prevent this metabotic disorder.
La fiebre de leche es un desbalance en el metabolismo del calcio que afecta especiaimente a las vacas de alta producción. Su origen se basa en una reducción de la capacidad de los receptores hormonales para activar los mecanismos encargados de mantener la homeostasis del calcio en el organismo. Entre los factores que predisponen a este desbalance están la dieta, la edad del animal, la raza, el nivel de producción y los factores individuales. Tiene una incidencia global de 3 a 4% y una baja mortalidad; sin embargo puede estar asociada a una serie amplia de enfermedades. El tratamiento con borogluconato de calcio da excelentes resultados, especialmente si el animal se trata en las primeras fases del desbalance. Si los niveles de calcio llegan a ser inferiores a 5mg/100mL de plasma el animal muere. La alimentación con dietas pobres en calcio durante las últimas tres semanas de la gestación y el suministro de dietas ricas en este elemento duranle la lactación ayudan a prevenirlo. El suministro de dosis altas en vitamina D en la d¡eta o la inyección de análogos de la vitamina D antes del parto, también ayudan a prevenir este desbalance. En la actualidad se usan sales acidificantes con este objetivo.
En revista Nutrición Animal Tropical, vol. 1, no. 1 (enero-junio 1994)
Descripción basada en el contenido visto el 29 de agosto, 2025